Registro de fraturas por acidente de motocicleta de um hospital secundário na região do Médio Solimões – AM: retrospectiva de 20 anos - Chaves, Angelne Dantas (Brasil, 2021)
Objective: To carry out a retrospective survey of fractures in victims of motorcycle accidents treated in the Orthopedics sector at Hospital Regional de Coari Mayor Dr. Odair Carlos Geraldo - AM, from August to December 2020. Method: This is an epidemiological study retrospective and descriptive cohort, with data collection from a document base. Data collection was carried out at the Medical Archive of the Dr. Odair Carlos Geraldo Regional Hospital (Coari – AM), from August to December 2020. The criteria established for the inclusion of the studies were: All medical records and radiological reports of patients who were victims of traffic accidents involving motorcycles attended by the Orthopedics and Traumatology sector, and who were aged 18 years or over. The medical records and radiological reports were incomplete, illegible or with conflicting information. Result: Based on the files of the “Medical Archive of the Regional Hospital Dr. Odair Carlos Geraldo (Coari – AM)”, data were collected from 980 medical records regarding fractures resulting from motorcycle accidents. From the studied medical records, it appears that most cases were male (69.38%), with a mean age of ±48.53 years, with a predominance in the age group between 18 and 28 years (54.89), where 98.46% of the cases were individuals from Coari. Conclusion: Most of the fractures victimized young individuals, who were in full working capacity. Such patients will invariably require prolonged time off work, resulting in social security expenses and significant changes in their daily routines. From the analysis of what was exposed in the data presented, we concluded that our study was similar to the national literature consulted.